2002
DOI: 10.1074/jbc.m205566200
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Biological Characterization of Heterocyclic Inhibitors of the Hepatitis C Virus RNA-dependent RNA Polymerase

Abstract: The hepatitis C virus (HCV) NS5B protein encodes an RNA-dependent RNA polymerase (RdRp), the primary catalytic enzyme of the HCV replicase complex. We established a biochemical RNA synthesis assay, using purified recombinant NS5B lacking the C-terminal 21 amino acid residues, to identify potential polymerase inhibitors from a high throughput screen of the GlaxoSmithKline proprietary compound collection. The benzo-1,2,4-thiadiazine compound 1 was found to be a potent, highly specific inhibitor of NS5B. This age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
157
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(162 citation statements)
references
References 26 publications
5
157
0
Order By: Relevance
“…The benzo-1,2,4-thiadiazines (compounds 1 and 4) were shown to be potent inhibitors of the HCV RdRp with biochemical IC 50 values between 80 and 100 nM and cell-based IC 50 values around 500 nM (1). Calorimetry studies confirmed a direct interaction of these compounds with the viral polymerase and a window of selectivity for nucleic acid interaction.…”
Section: Single Cycle Synthesismentioning
confidence: 75%
See 2 more Smart Citations
“…The benzo-1,2,4-thiadiazines (compounds 1 and 4) were shown to be potent inhibitors of the HCV RdRp with biochemical IC 50 values between 80 and 100 nM and cell-based IC 50 values around 500 nM (1). Calorimetry studies confirmed a direct interaction of these compounds with the viral polymerase and a window of selectivity for nucleic acid interaction.…”
Section: Single Cycle Synthesismentioning
confidence: 75%
“…: 610-240-8207; Fax: 610-240-4064; E-mail: rsarisky@cntus.jnj.com. 1 The abbreviations used are: HCV, hepatitis C virus; NS5B, nonstructural protein 5B; RdRp, RNA-dependent RNA polymerase; nt, nucleotide(s); SPR, surface plasmon resonance; RU, relative units; PFA, phosphonoformic acid; TNTase, terminal transferase; 3Ј-rdGTP, 3Ј-ribodeoxy-GTP. tion, a direct initiation assay, was established.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure of the NS5B apoenzyme and the NS5B-RNA complex reveals the characteristic right hand architecture of polymerase enzymes, comprising three distinct domains (palm, thumb, and finger) encircling the enzyme active site located in the palm domain (3-6). The structural and biochemical characterization of HCV NS5B polymerase can provide a basis for drug design efforts, and the elucidation of the mechanism of inhibition can guide the optimization of inhibitor efficiency against wild-type and resistant mutants.Among the extensively investigated non-nucleosides documented to inhibit the RdRp activity of HCV NS5B, derivatives of various benzofuran and benzothiadiazine have been reported to bind to allosteric binding sites in the palm domain of NS5B (7,8). The palm domain, whose geometry is conserved in virtually all DNA and RNA polymerases, contains catalytic aspartic acids responsible for the nucleotidyl transfer reaction.…”
mentioning
confidence: 99%
“…One of the reasons for the inefficient immunoprecipitation of the NS5B may also be the ability of the NS5B protein to oligomerize. Glu 18 and His 502 residues are critical for the oligomerization process of HCV RdRp (39).…”
Section: Resultsmentioning
confidence: 99%